2017
DOI: 10.1016/j.atmosenv.2016.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Responses of human health and vegetation exposure metrics to changes in ozone concentration distributions in the European Union, United States, and China

Abstract: The impacts of surface ozone (O 3) on human health and vegetation have prompted O 3 precursor emission reductions in the European Union (EU) and United States (US). In contrast, until recently, emissions have increased in East Asia and most strongly in China. As emissions change, the distribution of hourly O 3 concentrations also changes, as do the values of exposure metrics. The distribution changes can result in the exposure metric trend patterns changing in a similar direction as trends in emissions (e.g., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 101 publications
5
63
0
Order By: Relevance
“…In all three regions the low and medium percentiles increase, while the highest percentiles decrease from 1990 until 2013. This was also shown by Simpson et al (2014) based on observations for northern Europe and based on observations for Europe, US and East Asia by Lefohn et al (2017). Further, using hourly O 3 observations, Karlsson et al (2017) showed that reduced concentrations in northern Europe were restricted to the highest O 3 concentrations during summer daytime, while the increase in low and mid-range concentrations occurred during wintertime at both day and night.…”
Section: Trend Over the Periodmentioning
confidence: 64%
“…In all three regions the low and medium percentiles increase, while the highest percentiles decrease from 1990 until 2013. This was also shown by Simpson et al (2014) based on observations for northern Europe and based on observations for Europe, US and East Asia by Lefohn et al (2017). Further, using hourly O 3 observations, Karlsson et al (2017) showed that reduced concentrations in northern Europe were restricted to the highest O 3 concentrations during summer daytime, while the increase in low and mid-range concentrations occurred during wintertime at both day and night.…”
Section: Trend Over the Periodmentioning
confidence: 64%
“…With the threshold variable already defined, the maximum (x max ) and minimum (x min ) values of this variable are determined. Threshold value is calculated based on Equation (2).…”
Section: Statistical Modelmentioning
confidence: 99%
“…It is a secondary pollutant (it is not directly emitted), generated by chemical reactions that occur in the atmosphere between primary air pollutants (nitrogen oxides-NO x -and volatile organic compounds-VOCs) catalyzed by sunlight [1]. The impact of this air pollutant has been studied in different areas [2][3][4][5]. Concerning human health, O 3 can cause injuries to airway epithelial cells (and lung diseases such as asthma), hyperplasia, headaches, and nausea, particularly in sensitive people, such as children and elderly [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Karlsson et al, 2007b;Lal et al, 2017) or region-specific (e.g. Karlsson et al, 2017;Lefohn et al, 2017). TOAR's collation of ozone data provides the first opportunity to understand presentday distribution and trends relevant to vegetation on a global scale.…”
Section: Introductionmentioning
confidence: 99%